Thyrotoxic Hypokalemic Periodic Paralysis Triggered by Dexamethasone Administration - Waraporn Polamaung (Acta Medica, 2020)
Thyrotoxic hypokalemic periodic paralysis (THPP) is a disease characterized by recurrent episodes of muscle weakness due to intracellular potassium shifting in the presence of high levels of thyroid hormone. It occurs more commonly amongst young Asian men with underlying Graves’ disease. Attacks are commonly precipitated by ingestion of carbohydrate-rich meals or alcohols, stress or strenuous exercise. Herein, we describe an adult Thai man suffering from a hypokalemic periodic paralysis attack after receiving a dexamethasone injection. The diagnosis of Graves’ disease was confirmed by his thyroid function test and a presence of thyrotropin-receptor antibody. His weakness and hypokalemia responded well to potassium supplement and a non-selective beta blocker, while his thyrotoxicosis was initially controlled by an anti-thyroid medication and subsequently with a subtotal thyroidectomy. Clinicians should beware of this manifestation when administering steroids in the thyrotoxic patients, especially of Asian male descent.